Microwave mixer technology and applications - Henderson, Bert; Camargo, Edmar (Artech House, 2013)
Although microwave mixers play a critical role in wireless communication and other microwave applications employing frequency conversion circuits, engineers find that most books on this subject emphasize theoretical aspects, rather than practical applications. That's about to change with the forthcoming release of Microwave Mixer Technology and Applications. Based on a review of over one thousand patents on mixers and frequency conversion, authors Bert Henderson and Edmar Camargo have written a comprehensive book for mixer designers who want solid ideas for solving their own design challenges. Many of the important and most interesting patents and related circuits are discussed in the several application oriented chapters. In addition, important contributions from the technical literature are included to provide a solid theoretical foundation. This book contains both introductory and advanced material about active and passive mixers that use bipolar transistor, FET, or diode switching devices. Theory and design details are presented for dozens of important mixer designs, with practical application information derived from the authors' decades of experience